EPIDEMIOLOGY AND CLINICAL CHARACTERISTICS OF HENOCH-SCHÖNLEIN PURPURA ASSOCIATED WITH EPSTEIN-BARR VIRUS INFECTION - Hongbo Hu; Jiangang Wu; Ying Cheng; Jian jun Li (Mediterranean Journal of Hematology and Infectious Diseases)
Introduction: Henoch-Schönlein purpura (HSP) is an immune-mediated vasculitis, and the formation of immune complexes may be triggered by exposure to Epstein-Barr virus (EBV) infection.